Geopolitics of biodiversity: the case of patents in Colombia 1993-2014 - López Guzmán, Jorge Alberto (2017)
This article aims to explain one of the current conceptions of geopolitics, where the main actors are no longer the States, but the Multinational Enterprises, which, using geostrategic tools such as Intellectual Property Rights (IPR), commercialize and privatize derivatives of biodiversity . In this context, the case of patents of invention with biological and genetic resources in Colombia from 1993 to 2014 will be investigated.